Adaptasi Strategi Penawaran Produk yang Dilakukan Para Pedagang Pasar Seni Sukawati Pada Masa Pandemi Covid-19 - Santi, Ni Wayan Ayu; Indrayani, Luh; Irwansyah, M. Rudi (Universitas Pendidikan Ganesha, 2022)
Covid-19 appeared in the Province of Bali from the beginning of 2020, causing the community to try to make adaptations. The purpose of this study is to determine the adaptation of product supply strategies during the pandemic. The type of research used is descriptive qualitative research. In this study using data collection techniques in the form of observation and interviews. The data has been collected, it is analyzed through three stages, namely data reduction, data presentation, and conclusion drawing. Based on the results of the study, data obtained that there was an adaptation of the product supply strategy at the Sukawati Art Market in terms of products offered during the pandemic, in terms of sales techniques and in terms of follow-up when sales were completed.